Tinjauan Literatur Terhadap Perkembangan Kurikulum Pendidikan Matematika di Indonesia Dari Masa Ke Masa - Haq. MY, Annisa Husnul; Kusumah, Yaya S.; Dahlan, Jarnawi A. (Jurnal PEKA (Pendidikan Matematika), 2026)
ABSTRACT: In mathematics subjects, reviewing the development of the curriculum in Indonesia is a step in adapting to global dynamics in the aspect of education, student needs, and demands from the development of the times. Some examples of challenges faced by the development of the education curriculum in Indonesia from time to time are the lack of teacher readiness in adopting new approaches, the gap between implementation in the field and the concept, and inconsistencies between curricula. The purpose of the study is to analyze the development of the mathematics education curriculum in Indonesia from time to time. The writing of this journal uses a qualitative research type. The findings of the study are the development of the mathematics education curriculum in Indonesia from time to time starting from the 1994 Curriculum, KBK (2004), KTSP (2006), 2013 Curriculum, and the Independent Curriculum. Reviewed from the assessment, education starts from a written exam to a formative and holistic assessment. Furthermore, reviewed from student involvement in the 1994 curriculum, passive student involvement was found until the independent curriculum experienced an increase in student involvement to become very active personally. In terms of the role of teachers, there has also been an increase in the development of the curriculum, namely starting from the dominant method of lectures, facilitators, and collaborating facilitators. Furthermore, the flexibility of the curriculum has also increased from the "Low" category in the 1994 Curriculum to the "Very High" category in the independent curriculum ABSTRAK: Pada mata pelajaran matematika meninjau terkait dengan perkembangan kurikulum di indonesia merupakan langkah dalam beradaptasi terhadap dinamika global pada aspek pendidikan, kebutuhan peserta didik, serta tuntutan dari perkembangan zaman. Beberapa contoh tantangan yang dihadapi dari perkembangan kurikulum pendidikan di indonesia dari masa ke masa ialah kurangnya kesiapan guru dalam mengadopsi pendekatan baru, kesenjangan antara impelemntasi di lapangan dengan konsep, serta inkosistensi antar kurikulum. Tujuan penelitian ialah menganalisis terkait dengan perkembangan kurikulum pendidikan matematika di indonesia dari masa ke masa. Penulisan dari jurnal ini menggunakan jenis penelitian kualitatif. Hasil temuan penelitian ialah perkembangan kurikulum pendidikan matematika di indonesia dari masa ke masa mulai dari Kurikulum 1994, KBK (2004), KTSP (2006), Kurikulum 2013, dan Kurikulum Merdeka. Ditinjau dari penilaian maka pada pendidikan dimulai dari adanya ujian tertulis hingga dilakukan penilaian formatif dan holistic. Selanjutnya ditinjau dari keterlibatan siswa pada kurikulum 1994 didapatkan keterlibatan siswa pasif hingga pada kurikulum merdeka mengalami peningkatan keterlibatan siswa menjadi sangat aktif secara personal. Ditinjau dari peranan guru juga mengalami peningkatan dari perkembangan kurikulum yaitu mulai dari metode dominan ceramah, fasilitator, dan kolaborator fasilitator. Selanjutnya dari fleksibilitas kurikulum juga mengalami peningkatan dari karegori “Rendah” pada Kurikulum 1994 hingga di kategori “Sangat Tinggi” pada kurikulum merdeka.